1965
DOI: 10.1111/j.1570-7458.1965.tb00849.x
|View full text |Cite
|
Sign up to set email alerts
|

POPULATIONS OF TETRANYCHUS ATLANTICUS McG. (ACARINA: TETRANYCHIDAE) ON SOYBEAN SUPPLIED WITH VARIOUS LEVELS OF NITROGEN, PHOSPHORUS, AND POTASSIUM1

Abstract: Populations of Tetranychus atlanticusMcGregor, on detached leaf discs from soybean plants in sand culture were greatly influenced by the amount of supplied nitrogen. Two nutrient formulae were used in which the balance of the ions were quite different. Increasing the nitrogen in either formula increased the population. The effects of supplied phosphorus or potassium seemed to depend on the interrelationship of ions in the nutrient solution.Varying the phosphorus concentration in one formula did not alter the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Rodriguez (1960) concluded that aphids, chinch bugs, lepidopterous larvae, scale insects, and mites all benefit either directly or indirectly from an increase in nitrogen in their food. This trend has been substantiated in more recent studies on mites (Cannon andConnell 1965, Storms 1969), aphids (van Emden 1966, Dixon 1970, lepidopterous larvae (SooHoo and Fraenkel 1966aand 1966b, Taylor and Bardner 1968, Feeny 1970, Schramm 1972, Wiseman et al 1973, Onuf 1976, bugs (McNeill 1973), and beetles (Taylor and Bardner 1968, Schramm 1972, Onuf 1976). These beneficial effects are variously manifested through increases in individual growth rate, longevity, fecundity, reproductive rate, andjor survivorship.…”
Section: Introductionmentioning
confidence: 69%
“…Rodriguez (1960) concluded that aphids, chinch bugs, lepidopterous larvae, scale insects, and mites all benefit either directly or indirectly from an increase in nitrogen in their food. This trend has been substantiated in more recent studies on mites (Cannon andConnell 1965, Storms 1969), aphids (van Emden 1966, Dixon 1970, lepidopterous larvae (SooHoo and Fraenkel 1966aand 1966b, Taylor and Bardner 1968, Feeny 1970, Schramm 1972, Wiseman et al 1973, Onuf 1976, bugs (McNeill 1973), and beetles (Taylor and Bardner 1968, Schramm 1972, Onuf 1976). These beneficial effects are variously manifested through increases in individual growth rate, longevity, fecundity, reproductive rate, andjor survivorship.…”
Section: Introductionmentioning
confidence: 69%
“…Aphids, chinch bugs, lepidopterous larvae and mites, for example, show increased growth rates, longevity and survival when they consume foods with elevated nitrogen content (Rodriguez 1960; Cannon and Connell 1965; Storms 1969; Soo Hoo and Fraenkel 1966; Van Emden 1966; Dixon 1970). …”
Section: Introductionmentioning
confidence: 99%
“…For decades, a mismatch in nitrogen content between insects and their food plants has been recognized to be a critical factor influencing herbivore success ( Slansky and Feeny 1977 ; McNeill and Southwood 1978 ; Mattson 1980 ; Denno and McClure 1983 ; Strong et al 1984 ; White 1993 ; Schindler and Eby 1997 ). Aphids, chinch bugs, lepidopterous larvae and mites, for example, show increased growth rates, longevity and survival when they consume foods with elevated nitrogen content ( Rodriguez 1960 ; Cannon and Connell 1965 ; Storms 1969 ; Soo Hoo and Fraenkel 1966 ; Van Emden 1966 ; Dixon 1970 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both species have similar thermal requirements but, T. atlanticus prefers extremely dry conditions [9]. Some differences were established in their response to host plant nutrient status [79]. The development of T. urticae is positively influenced by potassium content in the plant host, while T. atlanticus is positively influenced by content of phosphorus.…”
Section: Collected Species: Abundance and Importancementioning
confidence: 99%